Three Unique Facts About Lesson Study-Based Micro Teaching in Mathematics Learning Media Courses - Aziz, Saddam Al; Suherman; Dwina, Fitrani; Meutia Rani, Maulani; Silvia, Elvi; Irwandi (Universitas Negeri Padang, 2024)
Mathematics Learning Media courses prepare students to design and use effective media. This research aims to describe unique facts that emerge during lesson study-based microteaching, which is carried out in the context of mathematics learning. This method involves three stages: Plan, Do, and See, which allows students to collaborate and get feedback. Even though micro-teaching is proven to contribute to student skills, observations show that there are challenges, such as low critical and creative thinking skills and errors in carrying out apperception. The research results show that ineffective apperception activities, a lack of creativity in designing media, and students' ability to analyze information critically during learning are obstacles to learning objectives. This research recommends the need for more intensive guidance from lecturers to improve the quality of learning in the future.